Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/2332649218790989
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Student Debt and the Reproduction of the Fragile Black Middle Class

Abstract: A nascent literature recognizes that student loan debt is racialized and disproportionately affects youth of color, especially black youth. In this study, the authors expand on this research and ask whether black-white disparities in student debt persist, decline, or increase across the early adult life course, examine possible mechanisms for changes in racial disparities in student debt across early adulthood, and ask whether racial disparities in student debt contribute to black-white wealth inequality among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 42 publications
1
80
0
Order By: Relevance
“…It is not access to credit that thwarts the mobility of African American graduate and professional degree-earners; it is the degree of debt they must assume to earn their degrees. The historically high levels of debt incurred by African Americans who earn graduate degrees may inhibit their ability to support their children’s educational expectations, contributing to the well-documented fragility of the black middle class (Houle and Addo 2018; Landry and Marsh 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not access to credit that thwarts the mobility of African American graduate and professional degree-earners; it is the degree of debt they must assume to earn their degrees. The historically high levels of debt incurred by African Americans who earn graduate degrees may inhibit their ability to support their children’s educational expectations, contributing to the well-documented fragility of the black middle class (Houle and Addo 2018; Landry and Marsh 2011).…”
Section: Discussionmentioning
confidence: 99%
“…At least part of this disparity is attributable to many African American bachelor’s degree-holders’ borrowing for graduate school (Baum and Steele 2018). Black-white disparities in student debt tend to increase through early adulthood and are partially explained by differences in socioeconomic background and current adult socioeconomic status (Houle and Addo 2018).…”
Section: Graduate Student Debt and Inequalitymentioning
confidence: 99%
“…Based on the descriptive analysis of the Institute of Educational Sciences ( 2018 ) it is clear that not all students who have student loan debt obtained the same level of educational outcomes and those differences make drawing broad generalizations about labor market outcomes difficult. Houle and Addo ( 2019 ) detail the heterogeneity in student borrowers, particularly in minority populations and first-generation students.…”
Section: Literaturementioning
confidence: 99%
“…Finally, the harm caused by student loan debt weighs more heavily on African American students and their families, especially those from lower socioeconomic backgrounds (Houle & Addo, 2018; Jackson & Reynolds, 2013; Miller, 2017). Analyzing national longitudinal data for beginning postsecondary students in the 2003–2004 academic year followed up 12 years later, Miller (2017) found that African American/Black students were more likely to borrow than their White or Hispanic/Latino counterparts overall (78% vs. 57% and 58%, respectively), in 4-year public universities (87% vs. 60% and 65%), and private, for-profit institutions (95% vs. 90% and 84%).…”
Section: Trends In Student Loan Debt and Social Harmmentioning
confidence: 99%